Identifikasi Ektoparasit pada Ikan Lokal di Perairan Kota Palangka Raya - Maryani Maryani; Shinta S Monalisa; Toto Fransisco (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The study aims to identify the kind of infestation that infects local fisheries biota in the region of the city's waters and knows the prevalence and intensity of the ektoparasite found. The variables observed in this study were the types of parasites found in the fishery biota examined. Data obtained from observations in the form of prevalence and intensity were analyzed descriptively. Examined as many as eight species of birch (oxyeleotris marmorata), as many as 30 (botias macracanthus), one cork (channa striata), as many as 1 tail, and the patin fish (Scylla SPP), as many as 7. Traces of ectoparasites found include dactylogyrus sp, tricodina sp, lernea sp, epistylis sp, oodinium sp and octolasmis sp.